2021
DOI: 10.1039/d0ja00424c
|View full text |Cite
|
Sign up to set email alerts
|

High precision cadmium isotope analysis of geological reference materials by double spike MC-ICP-MS

Abstract: The effect of the DS ratio is evaluated and a correction approach is proposed to improve the accuracy and robustness of the proposed DS Cd isotope analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 34 publications
9
51
1
Order By: Relevance
“…Insufficient information is available about the threshold ratio of Pd because of the low levels in environmental and geological samples. However, our results for Pd were similar to those reported by Liu et al 25 For In, previously reported threshold ratios ranged from 10 −3 to 0.02, 25,28 and our result for In was similar to that reported by Peng et al 28 For Sn, different levels (0.02 to 0.5) of Sn-to-Cd ratios were reported by different laboratories, [26][27][28] and our result for Sn fell within that range. However, the interference trends of In and Sn in this study were different from those reported previously.…”
Section: Measurement Using Mc-icp-mssupporting
confidence: 92%
See 3 more Smart Citations
“…Insufficient information is available about the threshold ratio of Pd because of the low levels in environmental and geological samples. However, our results for Pd were similar to those reported by Liu et al 25 For In, previously reported threshold ratios ranged from 10 −3 to 0.02, 25,28 and our result for In was similar to that reported by Peng et al 28 For Sn, different levels (0.02 to 0.5) of Sn-to-Cd ratios were reported by different laboratories, [26][27][28] and our result for Sn fell within that range. However, the interference trends of In and Sn in this study were different from those reported previously.…”
Section: Measurement Using Mc-icp-mssupporting
confidence: 92%
“…This may be due to the fact that a high 113 In signal, produced from high In content, can disrupt the data correction of Cd. 28 For Sn, δ 114/110 Cd values decreased when the ratio of Sn to Cd increased, but the decrease was small. As mentioned earlier, the threshold ratios of Sn were different among different studies.…”
Section: Measurement Using Mc-icp-msmentioning
confidence: 92%
See 2 more Smart Citations
“…Cd and Sr isotope ratios were determined by a Nu Plasma II MC-ICP-MS (UK), and the instrumental operation parameters are listed in Table S1. The isotope samples were analyzed in 2% v/v HNO 3 , and the instrumental mass discrimination of Cd was corrected by the double-spike method, as reported in our previous work . For Sr isotope measurement, 87 Sr/ 86 Sr was corrected for instrument mass bias by normalizing to 86 Sr/ 88 Sr = 0.1194 …”
Section: Methodsmentioning
confidence: 99%